Nucleation and condensation characteristics of carbon dioxide in natural gas: A molecular simulation perspective. (15th June 2023) - Cao, Hengguang; Cao, Xuewen; Li, Hao; Zhao, Xiangyang; Cai, Weihua; Guo, Dan; Liu, Yang; Bian, Jiang
Highlights: The nucleation and growth pathways of CO2 clusters are illustrated at the molecular level. The thermodynamic and kinetic characteristics of the CO2 condensation are obtained. High pressure and low temperature increase nucleation rate and accelerate cluster growth. The differences between the simulated and theoretical values of nucleation rates are compared. Abstract: The potential of supersonic separators to remove CO2 from natural gas has received extensive attention. However, microscopic understanding of the condensation mechanism of CO2 in natural gas and the applicability of classical nucleation theory (CNT) is unclear. In this study, we investigated the condensation characteristics of CO2 gas by using computational fluid dynamics (CFD) and molecular dynamics (MD) simulations with a CH4 -CO2 mixture gas. The nucleation and growth pathways of CO2 are elucidated from the molecular scale. The results show that the Laval nozzle creates low-temperature conditions for CO2 liquefaction, and that reducing the inlet temperature and increasing the inlet pressure will create more favorable conditions for condensation. In the nucleation stage, CO2 gas molecules collide to form clusters, releasing large amounts of latent heat, leading to repeated condensation and evaporation of CO2 gas, and the stability of the clusters depends on the energy interactions with surrounding molecules. With higher initial pressure and lower cooling temperature, the nucleation phase duration is shortened, the nucleation rate increases, and the cluster growth is accelerated. In addition, CNT deviates from the MD simulation results by 3 ∼ 4 orders of magnitude, and reasonable corrections to the CNT will be made subsequently by combining the results of many MD simulations.